Diagnóstico sobre tenencia responsablede animales de compañía en trece sectores del distrito de Tarapoto - provincia de San Martín - Chu Ramirez, Aura Cristina (2016)
In Peru, there are two realities regarding the care and handling of animals; a pet as an integral part of the family and the hundreds or thousands of homeless animals in the streets. The problem that generates bad pet ownership, focuses on two perspectives that are public health and animal abuse. This work has the general objective diagnosis of Responsible Pet Company in the homes of the Thirteen sectors Tarapoto district of tenure. The research was conducted in the thirteen sectors Tarapoto District: Partido Alto, Suchiche, Huayco, La Hoyada, Punta del Este, Cercado, Los Jardines, Comercio, Sachapuquio, 9 de Abril, Atumpampa, Tarapotillo, Circunvalación. The research design is sectional type, using a stratified random sampling with proportional fixation. We used surveys to 376 households randomly in the thirteen sectors Tarapoto district. It was concluded that in the district of Tarapoto there is a 63% of surveyed households owning pets, equivalent to 10,585 homes approximately, of which most are dogs (60%) and most owners have higher education level. The 62% of pets remain inside the home, feed more than twice daily (66%) with homemade food (38%). Most owners know about the timing of deworming (72%) and Zoonosis (96%), but they do have knowledge about Rabia (64%). Most have wormed more than a month ago (40%), pets have vaccines (68%), leading to walk your dogs (52%) and bathe with Veterinary products (66%). The pets make their depositions inside the home (56%), but if they 10 would do it in public areas, the owners wouldn´t collect it (52%). A large percentage of owners do not realize their reproductive control of their animals (63%), which is the cause of dropouts, stray dogs and accidents. It is noted that homeowners with higher education level are more responsible and have better knowledge, since they have more preparation and conditions for owning a pet